Temporal Trends in X-Ray Exposure during Coronary Angiography and Percutaneous Coronary Intervention - Cedric Davidsen; Kirsten Bolstad; Ellisif Nygaard; Kjell Vikenes; Svein Rotevatn; Vegard Tuseth (Journal of Interventional Cardiology)
Background. Percutaneous coronary intervention exposes patient and staff to ionizing radiation. Although staff only receive a small fraction of patient dose through scatter radiation, there are concerns about the potential health effects of repeated exposure. Minimizing both patient and occupational exposure is needed. Objective. This article investigates patient and operator X-ray exposure over time in coronary intervention in relation to upgraded X-ray equipment, improved shielding, and enhanced operator awareness. Materials and Methods. Data regarding irradiation time, patient dose, and patient characteristics were extracted from the Norwegian Registry for Invasive Cardiology (NORIC) for procedures performed from 2013 to mid-2019. Personal operator dosimetry records were provided by the Norwegian Radiation and Nuclear Safety Authority. Improved operator shielding and awareness measures were introduced in 2018. Results. In the period 2013 through June 2019, 21499 procedures were recorded in our institution. Mean dose area product (DAP) for coronary angiography decreased 37% from 2981 μGy·m2 in 2013 to 1891 μGy·m2 in 2019 (p<0.001). For coronary intervention, DAP decreased 39% from 8358 μGy·m2 to 5055 μGy·m2. Personal dosimetry data indicate a 70% reduction in operator dose per procedure in 2019 compared to 2013. The most pronounced reduction occurred after improved radiation protection measures were implemented in 2018 (−48%). Conclusions. This study shows a temporal trend towards considerable reduction in X-ray doses received by the patient and operator during cardiac catheterization. Upgraded X-ray equipment, improved shielding, and enhanced operator awareness are likely contributors to this development.